U1 snRNP-Dependent Function of TIAR in the Regulation of Alternative RNA Processing of the Human Calcitonin/CGRP Pre-mRNA - Zhu, Hui (American Society for Microbiology, 2003)
Alternative RNA processing of human calcitonin/CGRP pre-mRNA is regulated by an intronic enhancer element. Previous studies have demonstrated that multiple sequence motifs within the enhancer and a number of trans-acting factors play critical roles in the regulation. Here, we report the identification of TIAR as a novel player in the regulation of human calcitonin/CGRP alternative RNA processing. TIAR binds to the U tract sequence motif downstream of a pseudo 5′ splice site within the previously characterized intron enhancer element. Binding of TIAR promotes inclusion of the alternative 3′-terminal exon located more than 200 nucleotides upstream from the U tract. In cells that preferentially include this exon, overexpression of a mutant TIAR that lacks the RNA binding domains suppressed inclusion of this exon. In this report, we also demonstrate an unusual novel interaction between U6 snRNA and the pseudo 5′ splice site, which was shown previously to bind U1 snRNA. Interestingly, TIAR binding to the U tract sequence depends on the interaction of not only U1 but also U6 snRNA with the pseudo 5′ splice site. Conversely, TIAR binding promotes U6 snRNA binding to its target. The synergistic relationship between TIAR and U6 snRNA strongly suggests a novel role of U6 snRNP in regulated alternative RNA processing.